A fine structure study on osteogenesis of mesenchymal stem cells cultured with a 3D collagen scaffold. Issue 2 (2015) - Kumabe, Shunji; Nakatsuka, Michiko; Iwai, Rie; Ueda, Katsura; Matsuda, Yoshifumi; Morita, Shosuke; Iwai, Yasutomo
No abstract available